Partnership Marketing Counseling for Siwalan sugar in Pedak Village, Sulang District, Rembang Regency, Central Java - Riany Aulia Shabila; Achmad Hilal Madjdi; Mulyanto Mulyanto; Alif Catur Murti; Muhammad Imanuddin (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Pedak Village in Sulang District, Rembang Regency, is a village that produces the most agricultural commodities in the form of siwalan. This village is even nicknamed 1000 Bogor (siwalan). The siwalan tree produces sap that can be used as raw material for siwalan sugar. The community can produce 2,200 kg of siwalan sugar every day. The abundant production of siwalan sugar is still marketed conventionally by selling it to siwalan sugar collectors. However, collectors have not been able to accommodate all of the residents' siwalan production. In addition, the price of siwalan sugar sold to collectors is relatively low, IDR 18,000.00 per kg, even though the cost of siwalan sugar at the consumer level is IDR 27,000.00 - IDR 30,000.00 per kg. This relatively large price margin allows siwalan sugar artisans in Pedak Village to get optimal profits, so the Muria Kudus University Development Service Team took the initiative to introduce a marketing method for siwalan sugar so that the price margin sold by artisans and the price purchased by consumers is not too far apart. Artisans can also sell siwalan sugar products to a broader market segment. The proper marketing method for siwalan sugar is partnership marketing. This method is introduced to the community through the counseling of ideas. The marketing partner formed is the BUMD. This institution is expected to be able to accommodate siwalan sugar as a typical souvenir from Pedak Village, especially for the "1000 Bogor Tourism, Pedak Village". BUMD can also participate in UMKM product exhibitions organised by the government and the private sector